Phytochemical Screening and Evaluation of Anticancer Activity of Prunus persica(Linn) Batsch leaves in Breast Cancer Cell line (MDA-MB 231) and Cervical Cancer Cell line (HeLa) - Firdous Ahmad Bhat; Sabeeha Shafi; Khalid Majid Fazili; Nazia Hilal (International Journal of Pharma and Bio Sciences, 2020)
Breast cancer and cervical cancer are the most common causes of cancer mortality among women in India. While conventional anticancer treatments can help the affected patients, cells of vital organs such as the kidney, lungs, bladder and nervous system may suffer from side effects of chemotherapeutic drugs, so that it is necessary to search for alternatives. Scientific and research interest is drawing its attention towards naturally-derived compounds as they are considered to have less toxic side effects compared to current treatments such as chemotherapy. The present research work was conducted to investigate anticancer activity of Methanolic, Aqueous and Chloroform extract of leaves of Prunus persica on Breast cancer cell line(MDA-MB-231) and Cervical cancer cell line (HeLa) cultures, in vitro using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide MTTThe three extracts of the leaves of Prunus persica were tested for its inhibitory effect on MDA-MB-231 and HeLa cell lines. The cell lines were maintained in a 5% CO2 incubator at 37°C. Different concentrations of various extracts of Prunus persica in serum-free culture medium were freshly prepared and cytotoxic activity was evaluated using MTT assay. The findings of the current study showed the significant cytotoxic effect of the various extracts of leaves of Prunus persica. In this present study, chloroform extract of leaves of Prunus persica was found to possess most potent cytotoxic activity with IC50 of 6.6µg/ml followed by aqueous extract with IC50 15.15µg/ml followed by methanolic extract with IC50 76.19 µg/ml against MDA-MB-231 cell line. Against the HeLa cell line aqueous extract was found to be more cytotoxic with IC50 of 54.93µg/ml followed by moderately potent methanolic extract with IC50 of 77.41µg/ml followed by weakly anticancer chloroform extract with IC50 of 120.3 µg/ml. These results show that leaves of Prunus persica(Linn)Batsch possess potent anti cancer effect and for future perspective, it can be further confirmed by isolating the compounds responsible for the activity and studying the exact mechanism by which the plant possess this activity and confirm the results using in vivo animal models.